Pengaruh Aktivitas Scroll TikTok terhadap Sistem Reward Otak Anak Usia Sekolah Dasar: Studi Kasus di SDN 2 Berangah - Erwin Mardinata Utama (Journal of Science and Technology: Alpha, 2025)
This study aims to examine the impact of TikTok scrolling activity on the reward system of elementary school children's brains, focusing on fifth-grade students at SDN 2 Berangah. Repetitive scrolling behavior on the TikTok platform is suspected to trigger excessive dopamine release, potentially affecting children's concentration, learning motivation, and impulsive behavior. The research method used is descriptive qualitative, involving classroom observation, teacher interviews, and student questionnaires. The findings indicate that intensive TikTok usage leads to decreased learning focus and increased tendencies to seek instant stimulation. These results highlight the need for adaptive educational strategies in response to digital technology developments in elementary school environments.